Post-weaning social isolation of mice: A putative animal model of developmental disorders - Kinzo Matsumoto; Hironori Fujiwara; Ryota Araki; Takeshi Yabe (Elsevier, 2019)
Post-weaning social isolation of laboratory animals is known to induce many behavioural and neurochemical abnormalities, which resemble neuropsychiatric disorders such as depression and anxiety. Therefore, they can help provide a suitable animal model to investigate the pathophysiology of neuropsychiatric symptoms and explore potential drugs for the treatment of neuropsychiatric diseases. Our recent studies have demonstrated that post-weaning social isolation of mice for no less than one week causes behaviour changes such as reduced attention, impaired social affiliation behaviour, and impaired conditional fear memories. Our neuropharmacological analyses have revealed that these behavioural features are modulated by different neuronal mechanisms, suggesting that post-weaning social isolation of mice can help provide an animal model with comorbid symptoms of patients with developmental disorders, including attention-deficit hyperactivity disorder, autism spectrum disorder, and specific learning disability. In this review, we discuss the neuropharmacological features of developmental disorder-like behaviour induced by post-weaning social isolation in mice to offer new insights into the pathophysiology of developmental disorders and possible therapeutic strategies. Keywords: Social isolation rearing, Animal model, Developmental disorders, Epigenetics allopregnanolone